IMPLEMENTASI MODUL PELATIHAN PENCEGAHAN DAN PENANGGULANGAN OBESITAS UNTUK GURU UKS DAN PETUGAS KESEHATAN DI PUSKESMAS SISIR KOTA BATU - Hadisuyitno, Juin; Riyadi, B. Doddy; Suwita, I Komang (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2020)
Overweight and obesity are now a health problem in society. The role of stakeholder, especially in educational institutions, namely the Usaha Kesehatan Sekolah (UKS) in the obesity prevention and prevention program is very necessary from the beginning, namely the school period. The obesity prevention and prevention training program for health workers and UKS coaches has never been done by the Puskesmas Sisir. The purpose of this activity is to improve the knowledge and skills of teachers and health workers in the prevention and control of obesity and obesity in elementary school children. The method of training with lectures, demonstrations and practices can increase participants' nutritional knowledge from an average score of 51.7 to 83.4 and make the skills in measuring height and weight gain be better and more correct. The sustainability of this activity must involve the participation and commitment of various stakeholder as well as the activity of Puskesmas staff. Activities at school will be effective by involving teachers and students and also training students to be able to carry out these activities independently.